Tricuspid annular plane of systolic excursion to prognosticate acute pulmonary symptomatic embolism (TAPSEPAPSE study). (4th September 2018) - Lahham, Shadi; Fox, John C.; Thompson, Maxwell; Nakornchai, Tanyaporn; Alruwaili, Badriah; Doman, Ghadeer; May Lee, Shannon; Shafi, Amal; Shniter, Inna; Valdes, Victoria; Zhang, Lishi
Abstract : Introduction: The imaging standard for evaluation of acute pulmonary embolism (PE) includes a computed tomography pulmonary angiogram. Ultrasonography has shown promise in obtaining the tricuspid annular plane systolic excursion (TAPSE) measurements, which may be of clinical importance in patients with acute PE. The objective of this study is to evaluate the diagnostic capability of TAPSE measurements for patients with suspicion for acute PE. Methods: We prospectively enrolled patients who came to the emergency department with suspicion of acute PE. Each patient underwent a point‐of‐care sonogram where a TAPSE measurement was obtained, followed by computed tomography pulmonary angiogram. Based on the computed tomography pulmonary angiogram findings, patients were grouped into 3 categories: no acute PE, clinically insignificant acute PE, or clinically significant acute PE. Results: We enrolled 87 patients in this study. Twenty‐three (26.4%) of these patients were diagnosed with PE. Of patients with PE, 15 (65%) were found to have a clinically significant acute PE. Analysis of mean TAPSE measurements between patients with clinically significant acute PE and those with insignificant or no PE was 15.2 mm and 22.7 mm, respectively (P ≤ .0001). Following receiver operating characteristic curve analysis, optimum TAPSE measurement to identify clinically significant acute PE is 18.2 mm. A cutoff TAPSE measurement of 15.2 mm shows a sensitivity of 53.3% (95% confidence interval, 26.7%–80%) and a specificity of 100% (95% confidence interval, 100%–100%) for the diagnosis of a clinically significant PE. Conclusions: Our data suggest that TAPSE measurements less than 15.2 mm have a high specificity for identifying clinically significant acute PE.